Bibliometric Analysis of Sustainable Food Systems - Maria Claudia Diaconeasa; Alina Zaharia; Georgiana Raluca Lădaru; Steliana Mocanu (Amfiteatru Economic, 2024)
Following the development of sustainability-related topics, its connection with the food sector could not be overlooked. Therefore, the need for constructing a functioning sustainable food system has emerged. This piece of research comes as a support for knowledge development regarding sustainable food systems, being a synthetic documentation source. Most of the studies on this topic have focused on the main parts of the food system and how they might turn to sustainability. However, recently, the focus has turned to the food system analysed as a whole puzzle. Therefore, the present paper aims at providing an overall image of the sustainable food system and its components as they appear in the worldwide recognised Scopus database indexed literature, up to this point, in order to identify what the common puzzle pieces in different authors perspectives are and to what extent has the interest of authors increased regarding sustainable food systems. By using the VOSviewer application on a group of articles and book chapters provided by the Scopus database on the key topic of “sustainable food systems”, we constructed a correlation map of most used key terms. Thus, this paper indicates the main topics related to a sustainable food system, and the main research directions on this hot topic. The findings show that there is a considerable increase in the number of research papers on this topic, the first papers being published only around 2008. Also, the interest of authors regarding the research of both consumers and producers’ behaviours regarding sustainable development is on an ascending trend. By investigating the Scopus database on 21st of March, 2024 and through the analysis elaborated for the 1972-2024 time frame, we observed that the most used key words in the analysed content were: “knowledge” (125 ccurrences), “food security” (166 occurrences), “consumer” (220 occurrences) and “product” (121 occurrences), suggesting that finding a sustainable way of providing sustainable food choices and ensuring food security are current issued that bring up interest for scholars, and authorities alike.